Facing Precarity: Alliances, Resistance, and the Politics of Urban Exclusion - Marina Volpe (lo Squaderno, 2025)
The contemporary international scenario is increasingly defined by harsh contours: on the one hand, it is becoming more closed off both internally and externally; on the other, it is marked by phenom- ena of forced displacement, acts of genocide, and the perpetuation of violence. The issue of migration, therefore, cannot be separated from the inviolable freedom of movement—a principle that capital- ism itself has, for centuries, selectively and discriminatorily upheld as one of its foundational tenets (Della Porta, 2018). This freedom must be reclaimed in its egalitarian application, irrespective of one’s origin or destination, and beyond the constraints of imposed legal categories.